The Effect of Sprint Training on Physical Fitness Tests of Elementary School Students - Joko Sulistyono; pipit fitria yulianto; michael andriano zulfikar; aldila aziz nur c (Physical Activity Journal (PAJU), 2025)
Numerous bacteriophages can infect humans; thus, it is essential to bolster immunity to sustain health and bodily resistance effectively. This research aims to assess their fitness following the Indonesian physical fitness test (TKJI) utilizing the designated tools. This study employs a mixed-method quantitative research strategy. This approach is employed to gather data via multiple minor assessments and interviews with pupils from Bororejo public elementary school. This data include (1) small run test data, (2) data from interviews with children and teachers, and (3) the author's data interpretation. The test sequences employed are: (1) 20-meter run test, (2) elbow hang, (3) sit-up, (4) vertical jump, and (5) 100-meter run. This study comprises 25 students, including 15 females and 10 males. The findings of this study suggest that the results for TKJI in the "very good" and "good" categories are 1 (37.5%) and 15 (47.5%), respectively. Additionally, the physical education teacher's interview revealed that the students lacked seriousness during the test, leading to subpar outcomes.